2017
DOI: 10.9729/am.2017.47.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Exosomes Using Different Types of Electron Microscopy

Abstract: Negative staining has been traditionally used for exosome imaging; however, the technique is limited to surface topology only and can cause staining artifacts. Therefore, to analyze the internal structure of exosomes, we employed a method of block preparation, thin sectioning, and electron tomography. In addition, an automatic serial sectioning technique with 15-nm thickness through focused ion beam was employed to observe the three-dimensional structure of exosomes of various sizes. Cryo-transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 17 publications
8
12
0
Order By: Relevance
“…Nano–Sight analysis of the EV pellets revealed a homogenous population of EVs less than 150 nm in diameter. This was further confirmed by TEM, where we observed an EV size range of 60–130 nm, and the classical cup–shaped morphology described with a similar staining method [ 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…Nano–Sight analysis of the EV pellets revealed a homogenous population of EVs less than 150 nm in diameter. This was further confirmed by TEM, where we observed an EV size range of 60–130 nm, and the classical cup–shaped morphology described with a similar staining method [ 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…The presence and purity of epididymosomes was further validated by staining with the EV-specific marker CD9 and absence of the cellular marker GAPDH (Figure 1B). Size analysis by nanoparticle-tracking indicated that the collected particles are 50-300 nm in diameter (Figure 1D), and imaging by transmission electron microscopy showed the typical cup-shaped structures of epididymosomes (Figure 1C, Supplementary Figure 1A) [18]. RNA profiling by high-resolution automated electrophoresis showed enrichment for small RNAs of different lengths, similar to previous studies on cauda epididymosomal RNA content (Supplementary Figure 1B) [2,13].…”
Section: Resultssupporting
confidence: 84%
“…In cryo-electron microscopy (cryo-EM), samples will be fixed by cryo-immobilization where waters are vitrified instead of ice crystal formation in the sample by liquid ethane cooling. Cryo-immobilizing allows samples to be preserved in their native hydrated state, thus avoiding artifacts commonly caused by conventional fixation method such as cup shaped EVs [46, 47]. Combined with immunogold labeling, cryo-TEM can image EVs containing proteins and track EV uptake by recipient cells [48], as well as distinguishing EV subgroups by their size [49, 50].…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…After cryo-immobilization, samples can also undergo freezing substitution with fixing and embedding reagents for the specimens to be imaged under traditional TEM in room temperature. Since cryo-EM yields superior sample quality and morphology preservation over traditional EM methods [47], it is increasingly being applied to study EVs.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%